Pengaruh Model Project Based Learning terhadap Hasil Belajar Peserta Didik pada Materi Fluida Statis - Dela Nandani Savitri; Syahrial Ayub; Susilawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the Project-Based Learning (PjBL) model on students’ learning outcomes in the topic of static fluids. The population of this study consisted of all Grade XI Science classes at SMAN 1 Gunungsari. The samples were selected using a purposive sampling technique, resulting in Class XI MIPA A as the experimental group and Class XI MIPA C as the control group. The research employed a nonequivalent control group design, in which the two groups received different treatments. The experimental group was taught using the Project-Based Learning model, while the control group received conventional instruction. Learning outcomes were measured in the cognitive domain, covering cognitive levels from C1 to C6. The instrument used was a multiple-choice test consisting of 22 items. The learning outcome data were analyzed using parametric statistics, specifically the pooled variance t-test, at a significance level of 5%. The analysis yielded a calculated t-value (tₕᵢₜᵤₙg) of 3.65 and a critical t-value (tₜₐᵦₗₑ) of 2.01. Since the calculated t-value was greater than the critical t-value, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Therefore, it can be concluded that the Project-Based Learning model had a significant effect on students’ learning outcomes in the topic of static fluids.